2021
DOI: 10.3389/fagro.2021.694333
|View full text |Cite
|
Sign up to set email alerts
|

AtMYB12-Expressing Transgenic Tobacco Increases Resistance to Several Phytopathogens and Aphids

Abstract: Phytopathogens and pests are two major factors that limit the growth of plants. The expression of a flavonoid regulator gene, AtMYB12(AT2G47460), has been reported to increase the endogenous flavonoid content of tobacco and tomato. Previous research has only focused on the regulation mechanism of v-myb avian myeloblastosis viral oncogene homolog (MYB) transcription factors under single stress conditions. Here, research showed that AtMYB12 was involved in regulating the resistance of tobacco to multiple biologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…Phenylpropanoid is a class of secondary metabolites synthesized from phenylalanine in plants, which mainly includes caffeoylquinic substances and flavonoids, such as caffeoylquinic acids (CQAs), quercetin, quercetin rutinoside (rutin), and kaempferol rutinoside [ 1 , 2 , 3 ]. Flavonoids play an important role in improving the resilience of plants against various biological and abiotic stresses [ 4 , 5 ]. Rutin, for instance, enhances plant resistance against a variety of bacterial diseases by activating the salicylic acid (SA) synthesis pathway and regulating the expression of disease resistance genes, such as NPR1 [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Phenylpropanoid is a class of secondary metabolites synthesized from phenylalanine in plants, which mainly includes caffeoylquinic substances and flavonoids, such as caffeoylquinic acids (CQAs), quercetin, quercetin rutinoside (rutin), and kaempferol rutinoside [ 1 , 2 , 3 ]. Flavonoids play an important role in improving the resilience of plants against various biological and abiotic stresses [ 4 , 5 ]. Rutin, for instance, enhances plant resistance against a variety of bacterial diseases by activating the salicylic acid (SA) synthesis pathway and regulating the expression of disease resistance genes, such as NPR1 [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The other hand, tectorigenin may not trigger the rice immune response or trigger the responses independent of the resistance to R. solani . Previous studies had revealed that flavonoid regulator genes of AtMYB12 and OsF3H could negatively resist to some pathogens or pest, but positively resist to others (Ding et al ., 2021; Wu et al ., 2022). Ideally, more pathogen types can be tested here.…”
Section: Discussionmentioning
confidence: 99%
“…AtMYB12 overexpression improves pathogen resistance in transgenic tobacco plants ( Ding et al, 2021 ). In transgenic tobacco, AtMYB12 induces the production of flavonoid compounds, such as rutin, as well as reactive oxygen species, H 2 O 2 , and NO ( Pandey et al, 2015 ; Ding et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…AtMYB12 overexpression improves pathogen resistance in transgenic tobacco plants ( Ding et al, 2021 ). In transgenic tobacco, AtMYB12 induces the production of flavonoid compounds, such as rutin, as well as reactive oxygen species, H 2 O 2 , and NO ( Pandey et al, 2015 ; Ding et al, 2021 ). Similar to tobacco, our results revealed that the genes involved in pathogen resistance pathways ( Figure 4 ), defense-associated plant hormone signaling ( Figure 4 ), and WRKY TFs ( Figure 5 ) were significantly enriched in AtMYB12 -OX hairy roots.…”
Section: Discussionmentioning
confidence: 99%